KNOWLEDGE AND AWARENESS LEVEL OF ATOPIC DERMATITIS AMONG ADULTS LIVING IN SAUDI ARABIA (CAHIERS MAGELLANES-NS, 2024)
Background: Atopic dermatitis, also known as atopic eczema, is a common chronic-relapsing, inflammatory, and itchy eczematous skin disease that affects both adults and children. Asthma, food allergies, and allergic rhinitis are all related to atopic dermatitis, and having atopy in the family considerably increases the likelihood of developing this disease. Our study aims to assess knowledge and awareness of Atopic Dermatitis among adults living in Saudi Arabia.Methodology: This is an observational cross-sectional study that was conducted in Saudi Arabia during 2023. The sample size was estimated by Raosoft with a confidence level of 95% and a margin of error of 5%. The minimum sample size was 385. The data was collected through a standardized clear questionnaire, and its analysis was done using SPSS version 25.Results: Knowledge score showed that the largest proportion of individuals or entities falls within the moderate level category, accounting for 48.6%. Furthermore, the data indicates that 44.0% participants are classified as low level. Conversely, the high-level category represents 7.3% of the participants. Awareness score showed that the majority of the population falls into the low level, accounting for 81.5% of the total sample. On the other hand, the data also reveals that 16.0% of participants have an average level of awareness. Additionally, the data shows that only 2.5% of the participants have a good level of awareness. Relationship between eczema and quality of life score showed that the majority of individuals (51.6%) reported a low relationship between eczema and quality of life score. Additionally, 22.9% of individuals reported an average relationship between eczema and quality of life score, while 25.4% reported a good relationship between eczema and quality of life score.Conclusion: In conclusion, the Saudi general population exhibited poor knowledge and awareness levels towards eczema. Addressing the knowledge and awareness level of atopic dermatitis among adults living in Saudi Arabia is a critical step towards improving the health and well-being of those affected by this condition.